Barotraumatic Orbital Emphysema in Divers: Comprehensive Review with Case Series - Kodura, Alicja; Paluchowska, Joanna; Mordarska, Milena; Łozowski, Jan; Piwowarczyk, Alicja; Białas, Julia; Gołąbek, Natalia; Piątek, Przemysław; Merc, Artur; Szymański, Łukasz (Quality in Sport, 2026)
Aim. The aim of this paper is to outline the pathophysiological mechanisms underlying orbital emphysema in the context of barotrauma, which may occur in divers, to discuss the associated symptoms, diagnostic evaluation, and management, and to present the clinical cases described in the literature. Material and methods. The research methods applied included a systematic review of the PubMed, ResearchGate and Cyfrowa Biblioteka Medyczna UJCM databases, as well as other relevant sources, using the keywords: “orbital emphysema”, “diver”, “dive”, “scuba diving”, “eye barotrauma”, “paranasal sinuses anatomy”, “orbit anatomy”. Summary. Orbital emphysema refers to the presence of air within the orbital cavity, most often resulting from fractures of the orbital walls or barotrauma. Its clinical presentation varies from mild eyelid swelling and crepitus to more severe manifestations such as proptosis, restricted ocular mobility, or elevated intraorbital pressure. Management is conservative in most cases, with spontaneous resolution occurring over several days to weeks; however, urgent decompression may be required if orbital compartment syndrome develops. Among divers, only mild forms of orbital emphysema have been reported to date. Preventive measures include proper pressure equalization during diving, avoidance of forceful Valsalva maneuvers, and refraining from diving during episodes of sinus infection. Conclusions. Barotrauma-related risk increases when pressure equalization is impaired, the osteomeatal complex is obstructed, or minor facial injuries create pathways for air to enter the orbit during pressure changes. This review outlines the main features of orbital emphysema and its clinical manifestations in divers. Given the limited number of published cases, the condition is insufficiently described and requires further investigation.